A single-center intervention to discontinue postoperative antibiotics after spinal fusion. (4th March 2018) - Lewis, Ariane; Lin, Jessica; James, Herbert; Krok, Anne Clara; Zeoli, Nicole; Healy, Janine; Lewis, Tyler; Pacione, Donato
Abstract: Introduction: Postoperative antibiotics (PA) are often administered to patients after instrumented spinal surgery until all drains are removed to prevent surgical site infections (SSI). This practice is discouraged by numerous medical society guidelines, so our institutional Neurosurgery Quality Improvement Committee decided to discontinue use of PA for this population. Methods: We retrospectively reviewed data for patients who had instrumented spinal surgery at our institution for seven months before and after this policy change and compared the frequency of SSI and development of antibiotic related complications in patients who received PA to those who did not (non-PA). Results: We identified 188 PA patients and 158 non-PA patients. Discontinuation of PA did not result in an increase in frequency of SSI (2% of PA patients vs. 0.6% of non-PA patients, p = .4). Growth of resistant bacteria was not significantly reduced in the non-PA period in comparison to the PA period (2% in the PA period and 1% in the non-PA period). The cost of antibiotics for PA patients was 5, 499.62, whereas the cost of antibiotics for the non-PA patients was 0. On a per patient basis, the cost associated with antibiotics and resistant infections was significantly greater for patients who received PA than for those who did not (median of 26.32 with IQR 9.87-46.06 vs. median of 0 with IQR 0-0; p < .0001). Conclusion: After discontinuing PA for patients who had instrumented spinal procedures, we did not observe an increase in the frequency of SSI. We did, however, note that there was a non-significant decrease in the frequency of growth of resistant organisms. These findings suggest that patients in this population do not need PA, and complications can be reduced if PA are withheld.